#36: A Review of Maternal and Neonatal Characteristics and Outcomes in Pregnant Women with Serious Infectious Complications from Injection Drug Use. (28th June 2021) - Hastings, Lindsey; Leedy, Nicole; Cari, Evelyn Villacorta; Henderson, J T; Porterfield, J Z; Thornton, Alice
Abstract: Background: Pregnant people who inject drugs (PWID) and their infants are unique populations that have emerged from the opioid epidemic. Numerous studies have evaluated vertical transmission of HIV, HCV, sequelae of neonatal abstinence syndrome, and maternal and fetal mortality in these mother-infant dyads; however there still remains a large knowledge gap regarding how serious infections in pregnant PWID affect more proximal outcomes such as fetal and maternal distress leading to preterm delivery, risk of neonatal sepsis, need for invasive diagnostic procedures to rule-out neonatal sepsis such as lumbar puncture, neonatal intensive care unit (NICU) admission, and potential consequences of prolonged intrauterine antibiotic exposure. Methods: We identified pregnant PWID ≥18 years old with serious infectious complications (defined as (sepsis, endocarditis, osteomyelitis, epidural abscesses, septic arthritis/bursitis, thrombophlebitis, and skin and soft tissue infections requiring IV antibiotics) admitted between 2017–2018 to the University of Kentucky Medical Center and their neonates treated at Kentucky Children's Hospital. Patients were identified using positive urine or serum pregnancy test results, IVDU-associated ICD9/10 codes, infectious disease, neonatology, and obstetrics notes. Results: 261 women with infectious complications from IVDU were identified, 25 were pregnant and 16 dyads were able to be matched with identification of 14 viable neonates born at the University of Kentucky. Mean maternal age was 31 years and median 30 years. Mean gestational age (GA) at time of admission was 25 weeks with median 29 weeks. Sepsis was the most common complication reported 18 (72%) followed by endocarditis 11 (44%). Staphylococcus aureus was the most isolated organism (16) 64% with 12 (48%) of isolates identified as MRSA and MSSA comprising 4 (16%). 96% were screened for HCV, with 72% HCV antibody positive and 32% with detectable viral load. There was 1 reported maternal death, 1 spontaneous abortion and 2 intrauterine fetal demises (IUFD) in the 3 rd trimester and no neonatal deaths. Average GA at time of delivery was 33 weeks with median 36 weeks. 6 (42%) were routine deliveries with 3 (22%) deliveries for emergent maternal indications and 5 emergent deliveries for fetal indications (36%). 12 neonates (86%) required NICU admission with average length of stay 17 days and median 10 days. 10 (71%) underwent limited sepsis screen with 9 (64%) receiving at least 48 hours of antibiotics and 3 (22%) receiving an extended course. However none of the blood cultures yielded any organisms. All passed their hearing screening and had no evidence of renal dysfunction or cytopenias. Conclusions: Pregnant PWID dyads may be at increased risk for morbidity and mortality secondary to infectious complications of IVDU. The majority of neonates were delivered early for either fetal distress or maternal distress. 2 mothers suffered IUFD in the 3 rd trimester and the majority of the neonates required NICU admission (86%) due to prematurity-related factors, concern for neonatal abstinence syndrome or concern for infectious complications. Over half received 48+ hours of antibiotics in the NICU however none of the neonatal blood cultures yielded an organism. Larger cohort studies are needed to better ascertain risk in these expanding populations.